2017
DOI: 10.1101/145714
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chondroitin Sulfate Flourishes Gut Sulfatase-Secreting Bacteria To Damage Mucus Layers, Leak Bacterial Debris, And Trigger Inflammatory Lesions In Mice

Abstract: Background: An interaction of the food types with the gut microbiota changes is deeply implicated in human health and disease. To verify whether animal-based diets would lead to gut dysbiosis, systemic inflammation and inflammatory pathogenesis, we fed mice with chondroitin sulfate (CS), a sulfate-containing O-glycan naturally occurring in livestock and poultry products, and monitored the dynamic changes of microbial flores, inflammatory signatures, and pathogenic hallmarks. Results: A metagenomic gut microbio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
0
7
1
Order By: Relevance
“…Shewanella and Halomonas along with other bacteria to be increased in the gut microbiome of mice fed with chondroitin sulfate. This has been associated with gut inflammation as well as joint inflammation, leading to the hypothesis that the change in the gut microbiome contributes to the proinflammatory state (Liao et al, 2017). Despite other studies identifying this genus as a potential contaminant, we found no evidence of such in our negative control reactions.…”
Section: Identified Bothcontrasting
confidence: 64%
“…Shewanella and Halomonas along with other bacteria to be increased in the gut microbiome of mice fed with chondroitin sulfate. This has been associated with gut inflammation as well as joint inflammation, leading to the hypothesis that the change in the gut microbiome contributes to the proinflammatory state (Liao et al, 2017). Despite other studies identifying this genus as a potential contaminant, we found no evidence of such in our negative control reactions.…”
Section: Identified Bothcontrasting
confidence: 64%
“…Monk et al reported that Prevotella and S24–7 are carbohydrate fermenting and short chain fatty acid (SCFA) production bacteria [50]; SCFA can enhance the barrier function of colonic epithelium [51]. Rikenella was sulfatase-secreting bacteria [52], which induced the increase levels of bacterial endotoxinemia and chronic low-grade inflammation [53]. It was suggested that the changes of intestinal flora decreased inflammation and enhanced the mucus/epithelial barrier integrity in DMDJP100 group.…”
Section: Discussionmentioning
confidence: 99%
“…CS.NM with a normal phenotype has more A. muciniphila , but less B. cereus . CS.HL suffering from slight hairless shows no overgrowth of B. cereus and A. muciniphila (Liao et al, 2017b ). Distinct gut microflora communities might be rapidly established in mice fed CS at identical doses and schedules.…”
Section: Proinflammatory Activity Of Cs-promoted Ssb and Anti- Inflammentioning
confidence: 99%
“…A pro- and anti-inflammatory activities of CS might reflect the temporal and spatial changes of lipopolysaccharide (LPS) content. We previously reported that peripheral (serum and muscle) LPSs declined to normal levels, and that visceral (hepatic and cardiac tissues) LPSs were elevated to maintain a pro-inflammatory state, or adipose and cerebral LPSs declined to maintain an anti-inflammatory state (Liao et al, 2017a , b ). Administration of of a relative high 1.2 mg/kg LPS dose led to anti-inflammatory peritoneal changes, and a relative low 0.25 mg/kg LPS dose caused pro-inflammatory visceral changes, suggesting that anti-LPS treatment reduced LPS in peritoneal but not visceral tissues (Gao et al, 2015 ).…”
Section: Proinflammatory Activity Of Cs-promoted Ssb and Anti- Inflammentioning
confidence: 99%